The Effect of Discounts, Promotions, and Purchase Intention, on Cosmetic Purchasing Decisions at the Equatorial Store, Bengkulu City - Indi Desti Dwi Putri; Oni Yulianti; Yuli Yusnita (Penerbit Jurnal Indonesia, 2023)
This research aims to determine the influence of discounts, promotions, and purchasing interest on cosmetic purchasing decisions at Khalutistiwa store in Bengkulu City. The population in this study was 134 people. Data is processed in the form of numerical data (numbers) using a Likert scale. The data collection method in this research is a questionnaire. The data was processed using SPSS Windows version 25. The data analysis method used quantitative methods, namely by using multiple regression analysis. The results of research using multiple regression analysis (Y = 12.374 + 0.406 influenced the decision to purchase cosmetics at Khatulistiwa store in Bengkulu city. The largest significant influence on purchasing decisions at Khatulistiwa store in Bengkulu City is the promotion variable with a standard beta coefficient of 349, followed by the discount variable with a standard beta coefficient of 184, then the discount, promotion, and purchase interest variables with a significant Fcount value of 17.036. From the results of this analysis, a conclusion can be drawn that promotion is the dominant factor that has the greatest influence on purchasing decision tendencies at Khatulistiwa store, in Bengkulu city.